"...who comes first: [Māori] interests or architectural interests?"*: Three Heritage Cases Challenging Identity and Institutions in New Zealand. Issue 2 (4th May 2018) - Schmidt, Tyson
Abstract: Māori are gaining increasing economic and political power in New Zealand. This article explores three cases where architecture has been the tangible centrepiece in the performance of heritage as this increasing power has been applied – as part of the demolition of Āniwaniwa visitor centre in Te Urewera, the construction and sale of Te Kupenga o te Mātauranga at the former Palmerston North Teachers College site, and the attempts to demolish the former Aotea Māori Land Court building in Whanganui. Each displays how the Authorised Heritage Dialogue (AHD) as defined by Laurajane Smith in Uses of Heritage is being challenged. In particular, the cases highlight how contested narratives relating to Māori and New Zealand architecture are revealed and negotiated as increasingly well-resourced Māori groups navigate sovereign frameworks, and how AHD institutions (government agencies and professional societies) react and adapt to the challenges. While common threads exist through the three cases, they are also sufficiently different to show that the challenges are not specific to a particular place or type of architecture. Given that Māori economic and political power is continuing to grow, finding ways to overcome these heritage challenges will be important if New Zealand's built environment is to effectively embrace Māori identity.